#TITLE_ALTERNATIVE# - ANNA MARTINA (NIM 13203024), FRANSISKA
A new topology of high ratio dc-dc converter is proposed. The dc-dc converter designed has a main advantage in its ability to convert input voltage to another level of output voltage in a high ratio without using an extremely high or low duty cycle on the switch. Analytical expressions for the output voltage and current ripple are derived and comparative evaluation to single phase and two phase chopper is done. Minimum energy stored is an additional criteria used to define the LC parameter. Validity of proposed analysis method is verified by simulation and experimental results.